Policy Analysis in the United States - Hird, John A. (Book collections on Project MUSE., 2018)
Policy Analysis in the United States brings together contributions from some of the world's leading scholars and practitioners of public policy analysis including Beryl Radin, David Weimer, Rebecca Maynard, Laurence Lynn, and Guy Peters.